Attivismo, politica e performance di italianità delle nuove generazioni - Liti, Giulia (Antropologia Pubblica, 2024)
This article focuses on activism and engagement in public space of children of migrants. In particular, it examines the case of the Shape Academy, a project of civic activism targeting citizens of foreign origin. The objective is to reflect on the different values attributed to citizenship and the possibilities of active participation of children of migrants. A significant aspect of the Shape Academy is the proximity to institutions. It was created within the European project SHAPE (SHaring Actions for the Participation and Empowerment of migrant communities and local authorities), funded by the European Commission. In Italy, the project activities were organised by CoNNGI (Coordinamento Nazionale Nuove Generazioni Italiane), a national networkdedicated to empowering the children of migrants, which works closely with institutions such as the Ministry of Labour and Social Policies. During the project, the participants had the opportunity to engage directly with politicians and institutional figures. From the analysis of the themes, the language and the reflections proposed within the Shape Academy it emerges a particular kind of engagement in public space implemented by the new generation activists. The direct interaction with institutions influences how the new generations present and position themselves in the political arena. Children of migrants are often not recognised as Italian, even when they were born and raised in Italy. In this context, they are called upon to question their role and ‘prove’ their Italian-ness, through performative practices that emphasise belonging to the national community and replicate the practices of political communication in Italy.